Analysis of Distribution Channels and Promotional Mix at PT Varia Usaha Fabrikasi - Putri, Raisa Adila (Indonesian Vocational Research Journal, 2024)
Distribution channels are all marketing channels or intermediaries through which goods and services (including transportation and storage) go from producers to industrial users and consumers. Companies must be good at selling products. Companies must be able to see market opportunities to sell their products not only in domestic or local markets, but also internationally. Promotion Mix is ​​a tool formed from a combination of advertising tools used by a company. In general, these promotional tools are related to each other, not separated, because they complement each other. Promotional mix or also called marketing mix is ​​a plan for carrying out promotional activities. The aim of this research is to analyze the implementation of distribution channels and sales promotions at PT Varia, a fabrication business. The research method used is a qualitative method. The research results show that the distribution and promotion mix strategy taken by PT Varia, a fabrication business, is the right strategy for a company in carrying out the distribution and promotion mix process.